The first representative of the fully aquatic leaf beetle genus Macroplea Samouelle, 1819 (Coleoptera, Chrysomelidae) in Turkey: Macroplea mutica (Fabricius, 1792), with notes on its biology, habitat, host plant and distribution - Türkgülü, Ibrahim; Ekiz, Ali Nafiz; Gök, Ali; Şen, Bülent (My University, 2011)
Macroplea Samouelle, 1819 is a small genus of fully aquatic leaf beetles distributed in the Palearctic. Up to now, none is recorded from Turkey, and in this paper, we report Macroplea mutica (Fabricius, 1792), from Turkey for the first time. We present important morphological characters of larvae, pupae and adults collected from Eastern Anatolia. We also noted the biology, habitat features, host plant associations and the current distribution of the species. The relatively large but fragmented distribution of M. mutica is discussed on the bases of restricted underwater locomotion and reduced ability of flight of the species. The importance of its existence in Anatolian refugium is evaluated with regard to the phylogeography of the species. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Morphology; New record; Palearctic; Phylogeography